Tinjauan Hukum Ekonomi Syariah terhadap Pengurangan Upah Jasa Para Pekerja Bangunan di Kota Bandar Lampung - Ahmad Aziz Rantissy; Eti Karini; Apriansyah (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the practice of wage reduction for construction workers at Harmoni Sukarame Baru Housing, Bandar Lampung City, from the perspective of Islamic economic law. The issue arises from wage deductions made by project supervisors without the workers’ consent, raising concerns about fairness, transparency and compliance with the principles of ijarah (ujrah) contracts. This research employs a qualitative approach with a descriptive method. Data were collected through field observations, in-depth interviews with construction workers and project supervisors and documentation. The data analysis technique uses an interactive model, including data reduction, data display and conclusion drawing, based on Islamic economic law principles. The findings indicate that wage deductions made without prior agreement and clear notification contradict the principles of justice, mutual consent (an-taradhin) and contractual clarity. This practice negatively affects workers’ welfare. Therefore, a transparent and fair wage system aligned with sharia principles is necessary.